Aortic thrombus causing ischemic bowel mimicking as necrotizing enterocolitis in a premature neonate: A case report - Chun Yi Ting; Juin Yee Kong; Lin Yin Ong; Shui Yen Soh; Abdul Alim Abdul Haium (Elsevier, 2016)
Spontaneous neonatal aortic thrombus is rare. Clinical presentation can vary depending on the location of the thrombus. We report a case of a premature infant with ischemic bowel likely due to an aortic thromboembolic event. The infant had presented with an acute abdomen, and underwent an exploratory laparotomy for concerns of worsening necrotizing enterocolitis. Intra-operative findings were suggestive of segmental ischemic small bowel with thrombosis of mesenteric vessels and a subsequent Doppler ultrasound revealed an infra-renal aortic thrombus. He was treated with subcutaneous enoxaparin, with effective reduction in thrombus size on serial scans. However, this treatment was complicated by bilateral subdural hematoma, and hence enoxaparin was discontinued. Aortic thrombus, although rare, should be considered in the differential diagnosis of an acute abdomen. Management of neonatal aortic thrombus remains controversial and further studies are required to aid clinicians in deciding the best management plan with minimal risk and optimal outcome.